Penal Mediation of Petty Theft Cases Towards Restorative Justice - Syauket, Amalia; Sriwidodo, Joko (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
Discussing legal inequality in the phenomenon of some cases of petty theft (gepriviligeerde diefsal) hurts the sense of justice in society. Because there is a conflict between legal certainty and justice. In the process of the criminal justice system, it takes a rather long and long time and sometimes even convoluted, so a legal breakthrough is needed using penal mediation. Penal mediation is closely related to restorative justice. While the spirit of penal mediation to realize restorative justice exists in each law enforcement institution for the reason of creating a sense of justice for witnesses so that the community is satisfied with the services carried out by investigators. The development of the idea of penal mediation cannot be separated from the development of the idea of restorative justice as one of the ideas of criminal law reform (penal reform), This qualitative research on normative juridical methods aims to find out how the form of penal mediation and the technical implementation carried out by law enforcement institutions, especially the Police Agency? The results of this academic study concluded that the form of penal mediation used in some cases of petty theft crimes at the Police Level is Victim Offender Mediation (VOM) with technical implementation through four phases. This VOM model is regarded as the most practical for implementation as it unites both parties, facilitating the accommodation of their interests to achieve restorative justice. Novelty: Political-legal construction in penal mediation arrangements as an attempt to adapt national legal development to global and international trends.